Australia 2024 - Reid, Sarah; Barber, Kat (Travel writer); D'Arcy, Jayne; Dragicevich, Peter; Ham, Anthony; Harding, Paul; Holden, Trent; Korteman, Jessica; Lockhart, Jessica; Maxwell, Virginia, 1962-; McLachlan, Craig, 1962-; Musau, Mwende Mutuli; et al. (Lonely Planet guidebooks., 2024)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime to Australia. Discover popular and off the beaten track experiences from surfing the waves on Byron Bay's iconic beaches to watching little penguins waddle ashore at the famous Penguin Parade, and touring the famous rock art sites of Kakadu National Park with an Aboriginal guide.--